2020
DOI: 10.3390/su12198189
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Person-Job Fit between Person-Organisation Fit and Intention to Leave the Job: Empirical Evidence from Pakistan

Abstract: The turnover of faculty members is a pressing problem that has adversely affected the performance and productivity of higher education institutions. The purpose of this study is to examine the direct effect of person-organisation fit (POF) and person-job fit (PJF) on faculty members’ turnover intentions. Furthermore, the study explores the mediating role of PJF between POF and turnover intention. Data collected from faculty members of public sector colleges (n = 250) were analysed using partial least squares s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 57 publications
2
17
0
1
Order By: Relevance
“…This finding implies that if employees’ attributes are compatible with the job characteristics, they are less likely to exhibit cynical attitudes toward organizations. In line with the present study, previous studies have also confirmed the direct influence of PJF on a variety of attitudinal variables (e.g., job satisfaction, organizational commitment, and intention to stay) ( Cable and DeRue, 2002 ; Vogel and Feldman, 2009 ; Saufi et al, 2020 ; Kakar et al, 2022 ; Samad et al, 2022 ). These studies suggest that when employees observe that their KSAs are identical to the job requirements and job resources are adequate enough to meet their needs and preferences (i.e., PJF), then they exhibit positive attitudes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding implies that if employees’ attributes are compatible with the job characteristics, they are less likely to exhibit cynical attitudes toward organizations. In line with the present study, previous studies have also confirmed the direct influence of PJF on a variety of attitudinal variables (e.g., job satisfaction, organizational commitment, and intention to stay) ( Cable and DeRue, 2002 ; Vogel and Feldman, 2009 ; Saufi et al, 2020 ; Kakar et al, 2022 ; Samad et al, 2022 ). These studies suggest that when employees observe that their KSAs are identical to the job requirements and job resources are adequate enough to meet their needs and preferences (i.e., PJF), then they exhibit positive attitudes.…”
Section: Discussionsupporting
confidence: 92%
“…), an organization may engender a sense of feeling among employees that their organization is supportive and caring. This perception of care and support will develop positive attitudes among them ( Saufi et al, 2020 ; Kakar et al, 2022 ) and thus reduce their cynical attitudes toward organizations. The finding that WLB practices relate negatively to OC is coherent with the work of Dysvik et al (2014) and Koon (2022) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Nuansa et al. (2018) and Saufi et al. (2020) stated that the direct influence of P-O fit on turnover intentions was not significant compared to when mediated by other variables such as organizational commitment.…”
Section: Introductionmentioning
confidence: 79%
“…By looking at the lack of research that focuses on higher education institutions and the negative implications of turnover intentions on the academic community, it is vital to investigate the factors that cause turnover intentions (Kakar et al. , 2021a, b; Saufi et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian lain yang dilaksanakan oleh (Octaviani, 2016), (Chandra & Indriyani, 2018) dan (Khalida & Safitri, 2018) menjelaskan jika variabel Person-Organization Fit pada Turnover Intention yang menunjukan output Person -Organization fit memberikan pengaruh negatif serta tidak signifikan pada Turnover Intention. Tetapi dalam penelitian (Saufi et al, 2020) menunjukan hasil bahwa Person -Organization Fit memberikan pengaruh yang negatif serta tidak signifikan pada Turnover Intention, yang dilakukan oleh akademis perguruan tinggi sektor publik di pakistan. Hal tersebut menjelaskan jika nilai Person-Organisasi Fit semakin meningkat, dapat Pengaruh person-organization fit dan motivasi kerja terhadap turnover intention melalui kepuasan kerja sebagai variabel mediasi Artika Dwi Puspitasari, Kusuma Chandra Kirana FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi | 466 menyebabkan nilai Turnover Intention yang semakin menurun (Samson, Maharani dan Suliystiorni, 2020).…”
Section: Pendahuluanunclassified